Internet connectivity disruption in Cameroon (Cameroon) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Cameroon. Data sourced from IODA.
Network Disruption Incident ID: CM-2026-0052. Severity: critical. Confidence: 67%